Thermal cycling induced room temperature aging effect in Ni-rich NiTi shape memory alloy. (1st March 2016) - Wang, Xiebin; Van Humbeeck, Jan; Verlinden, Bert; Kustov, Sergey
Abstract: This work shows that the characteristics of B19′ martensite transformation in Ni-rich NiTi alloys are rather stable during aging at room temperature after quenching from 1273 K. However, if transformation cycles between austenite and martensite are performed, the B19′ martensite transformation can be strongly suppressed following aging at room temperature. As the NiTi elements normally experience cyclic transformation in applications, this phenomenon has to be taken into account as a factor for the functional degradation of NiTi alloys. Possible mechanisms of the uncovered aging effect are discussed. Graphical abstract: